THE METHODOLOGYOF THE LESSON "THE EFFECT OF ASSEMBLY" ON COURSE "PSYCHO-PEDAGOGICAL BASES OF ASSEMBLY THINKING FORMATION OF STAGE DIRECTORS" - Elena G. Protsenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The author dwells upon the forms, methods and means of creative project "Effect of assembly", proving the need and the opportunity to use interactive teaching methods director’s theatrical performances and holidays. The author revealed substantial aspects, principles of organization of educational process, the main activities of the director theatrical performances and holidays. Creative projects defined by the author as the most effective form of education, allowing to realize the variety of objectives, contents, teaching methods, types of independent work of students in the classroom for the course "Psycho-pedagogical bases of assembly thinking formation of stage directors" directors in theatrical performances and holidays. The research shows that the organization of project activities in the lesson "Effect of assembly" a teacher's position also varies with the position of director and translator of knowledge to the position of organizer, assistant. Author suggests that the formation of the assembly thinking of bachelors in preparation Direction theatrical performances and holidays, creative atmosphere, establishing trust and mutual communication are fundamental of education.